2003
DOI: 10.1001/jama.290.5.612
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to Terrorism, Stress-Related Mental Health Symptoms, and Coping Behaviors Among a Nationally Representative Sample in Israel

Abstract: ContextThe terrorist attacks on Israeli society have been ongoing since September 2000. However, few studies have examined the impact of terrorism on nationally representative population samples, and no study has examined the psychological impact of ongoing terrorism in Israel.Objectives To determine the level of exposure to terrorist attacks and the prevalence of traumatic stress-related (TSR) symptoms, symptoms of posttraumatic stress disorder (PTSD), and sense of safety after 19 months of terrorism in Israe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

55
459
14
13

Year Published

2003
2003
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 573 publications
(547 citation statements)
references
References 18 publications
55
459
14
13
Order By: Relevance
“…People working or living in the region of the attacks felt more threatened, which is in line with most other studies (Hansen et al, 2013). However, some studies only found a weak association between perceived threat and level of exposure (Bleich et al, 2003; Cohen et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…People working or living in the region of the attacks felt more threatened, which is in line with most other studies (Hansen et al, 2013). However, some studies only found a weak association between perceived threat and level of exposure (Bleich et al, 2003; Cohen et al, 2006). …”
Section: Discussionmentioning
confidence: 99%
“…Although they were only a very small subgroup in our study, this finding is in line with other studies after terrorist attacks (Rubin et al, 2005; Schuster et al, 2001; Stein et al, 2004). Studies in Israel showed that populations associated with the offenders do not suffer less than the populations that are the explicit target of terrorists (Bleich et al, 2003; Cohen & Eid, 2007). It is however remarkable that violence ‘in the name of religion’ affects religious people the most.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations